High-performance liquid chromatographic determination of tiapride and its phase I metabolite in blood plasma using tandem UV photodiode-array and fluorescence detection - Nobilis, Milan; Vybíralová, Zuzana; Szotáková, Barbora; Sládková, Květa; Kuneš, Martin; Svoboda, Zbyněk (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2011)
New bioanalytical SPE-HPLC-PDA-FL method for the determination of the neuroleptic drug tiapride and its N-desethyl metabolite was developed, validated and applied to xenobiochemical and pharmacokinetic studies in humans and animals. The sample preparation process involved solid-phase extraction of diluted plasma spiked with sulpiride (an internal standard) using SPE cartridges DSC-PH Supelco, USA. Chromatographic separation of the extracts was performed on a Discovery HS F5 250 mm × 4 mm (Supelco) column containing pentafluorophenylpropylsilyl silica gel. Mobile phase (acetonitrile-0.01 M phosphate buffer pH=3, flow rate 1 ml min(-1)) in the gradient mode was employed in the HPLC analysis. Tandem UV photodiode-array→fluorescence detection was used for the determination of the analytes. Low concentrations of tiapride and N-desethyl tiapride were determined using a more selective fluorescence detector (λ(exc.)/λ(emiss.)=232 nm/334 nm), high concentrations (500-6000 pmol ml(-1)) using a UV PDA detector at 212 nm with a linear response. Each HPLC run lasted 15 min. Lower limits of quantification (LLOQ) for tiapride (N-desethyl tiapride) were found to be 8.24 pmol ml(-1) (10.11 pmol ml(-1)). The recoveries of tiapride ranged from 89.3 to 94.3%, 81.7 to 86.8% for internal standard sulpiride and 90.9 to 91.8% for N-desethyl tiapride.
Keywords: Animals; Solid Phase Extraction; sulpirid; Linear Models; mladý dospělý; Reproducibility of Results; vysokoúčinná kapalinová chromatografie; lidé; spektrofotometrie ultrafialová; lineární modely; fluorescenční spektrometrie; jaterní mikrozomy; reprodukovatelnost výsledků; limita detekce; tiapamil-hydrochlorid; Chromatography, High Pressure Liquid; Male; Tiapamil Hydrochloride; Young Adult; Spectrophotometry, Ultraviolet; Sulpiride; Microsomes, Liver; extrakce na pevné fázi; krysa rodu Rattus; Limit of Detection; zvířata; mužské pohlaví; Spectrometry, Fluorescence; Rats; Humans